2018
DOI: 10.21277/sw.v1i8.340
|View full text |Cite
|
Sign up to set email alerts
|

Study on Relationship Between Family Cohesion and Adaptability, and Quality of Life of Caregivers of Children With ASD

Abstract: <p><em>The present study aimed at exploring the status of family cohesion, adaptability and quality of life of caregivers of children with ASD, as well as the relationship between family cohesion </em><em>and </em><em>adaptability, and quality of life. One hundred and sixty-three caregivers of children with ASD from Sichuan province </em><em>in China </em><em>were investigated by the </em><em>Chinese vision of </em><em>Family A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Cohesion refers to the emotional connection among family members, while adaptability indicates the ability to change the family structure based on events that occur during the life cycle [ 9 ]. Family cohesion was found to be associated with lower maternal depressive symptoms [ 3 ] and to positively predict parents’ well-being and quality of life [ 10 , 11 , 12 ]. Families identified as high on family cohesion (i.e., enmeshed) could implement more positive coping strategies [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cohesion refers to the emotional connection among family members, while adaptability indicates the ability to change the family structure based on events that occur during the life cycle [ 9 ]. Family cohesion was found to be associated with lower maternal depressive symptoms [ 3 ] and to positively predict parents’ well-being and quality of life [ 10 , 11 , 12 ]. Families identified as high on family cohesion (i.e., enmeshed) could implement more positive coping strategies [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study was not in line with a study conducted by Lei where the results showed that research subjects with enmeshed family cohesion were 24.5% of the whole research subjects. [13] This study, which was not in line with Lei's study, is due to many factors that affect family cohesion, including gender, age differences, sibling group size, family structure, and the presence of both parents. [14] The highest number of schizophrenia patients with enmeshed family cohesion is probably due to the low autonomy of schizophrenia patients themselves.…”
Section: Table 1 Distribution Of Study Subjectsmentioning
confidence: 68%
“…Meanwhile, many parents have limited knowledge and parenting skills at the initial stage of ASD diagnosis (Decroocq et al, 2020). As parents gain more ASD‐related knowledge through support services like early intervention programs, they may become better equipped to navigate challenges and feel more satisfied in their parenting roles and with disability‐related services (Decroocq et al, 2020; Lei, 2018). Most of the children in this study received intervention after the ASD diagnosis, supporting the notion that early interventions targeting parenting skills are warranted to help parents care for their children with ASD and improve FQoL.…”
Section: Discussionmentioning
confidence: 99%